Effects of pseudoephedrine on maximal cycling power and submaximal cycling efficiency - Hodges, A. N.; Lynn, B. M.; Bula, J. E.; Donaldson, M. G.; Dagenais, M. O.; McKenzie, D. C. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: To study the effects of a therapeutic dose of pseudoephedrine on anaerobic cycling power and aerobic cycling efficiency. METHODS: Eleven healthy moderately trained males (VO (2peak) 4.4 +/- 0.8 L x min(-1) participated in a double-blinded crossover design. Subjects underwent baseline (B) tests for anaerobic (Wingate test) and aerobic (VO (2peak) test) cycling power. Subjects ingested either 60 mg of pseudoephedrine hydrochloride (D) or a placebo (P) and, after 90 min of rest, a Wingate and a cycling efficiency test were performed. During the cycling efficiency test, heart rate (HR) and VO(2) were averaged for the last 5 min of a 10-min cycle at 40% and 60% of the peak power achieved during the VO (2peak) test. RESULTS: There were no significant differences in peak power (B = 860 +/- 154, D = 926 +/- 124, P = 908 +/- 118 W), total work (B = 20 +/- 3, D = 21 +/- 3, P = 21 +/- 3 kJ), or fatigue index (B = 39 +/- 8, D = 45 +/- 5, P = 43 +/- 5%). There were no significant differences in HR at 40% power (D = 138 +/- 10, P = 137 +/- 10 beats.min-1) or 60% power (D = 161 +/- 11, P = 160 +/- 11 beats x min(-1). There were no significant differences in cycling efficiency at 40% power (D = 18.8 +/- 1.8, P = 18.5 +/- 1.8%) or 60% power (D = 20.3 +/- 2.0, P = 20.1 +/- 2.1%). CONCLUSION: A therapeutic dose of pseudoephedrine hydrochloride does not affect anaerobic cycling performance or aerobic cycling efficiency.